Comparative Assessment of the Spectrum of Etiological Factors of Liver Cirrhosis in Bukhara and Navoi Regions - Aslonova I. Zh. (Miasto Przyszłości, 2023)
The problem of liver cirrhosis (LC) is still one of the most exciting ones, due to the steady increase in the frequency of its spread, mainly in regions with low social al -economic development potential (1,3,5,7 ). The urgent situation should have been expected, because over the years, a package of medical and social factors gradually began to take root in these regions, predetermining the scale of development of chronic liver diseases (CLD). Many of them continue to dominate the spectrum of drugs that have a harmful effect on the liver to this day.